Non-contracting groups generated by (3,2)-automata - Davis, N.; Elder, M.; Reeves, L. (Algebra and Discrete Mathematics, 2014)
We add to the classification of groups generated by 3-state automata over a 2-letter alphabet given by Bondarenko et al., by showing that a number of the groups in the classification are non-contracting. We show that the criterion we use to prove a self-similar action is non-contracting also implies that the associated self-similarity graph introduced by Nekrashevych is non-hyperbolic.